Central banking in the emerging countries : a study of African experiments - Basu, Saroj Kumar (New York : Asia Pub. House, 1967)
The study is concerned with a review of the experiments in central banking that have been made in the newly independentt African colonies and dependencies during the decade 1955-1965
"Select Bibliography": p. 298-303.
obn21/01/2019
Loans
Keywords: Banks and banking, Central; Banks and banking, Central